PENGEMBANGAN PANDUAN TEKNIK DISPUTE IRRATIONAL BELIEF BERBASIS PODCAST UNTUK MENINGKATKAN PERENCANAAN KARIER MAHASANTRI KELAS AKHIR IBNU KATSIR 1 JEMBER - Muhammad Pandu Raziqin; Mudafiatun Isriyah; Weni Kurnia Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop a podcast-based guide to dispute irrational belief techniques to improve career planning for final year students at the Ibnu Katsir 1 Jember Islamic Boarding School. Mahasantri often face irrational beliefs that hinder career decision making. This technique aims to identify and challenge these beliefs so that students develop a more rational mindset. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects were final year students who experienced career confusion. Data collection was carried out through interviews, questionnaires and observations, with qualitative and quantitative analysis. The results show that the podcast-based guide is effective in helping student students understand and correct their irrational beliefs. The podcast medium has proven to be relevant, flexible and attractive to the younger generation, thereby increasing their understanding of rational career planning. It is hoped that this guide will be a solution in preparing students to make better career decisions in the future.